NF-κB signaling pathway in tumor microenvironment - Cao, Yaning; Yi, Yanan; Han, Chongxu; Shi, Bingwei (Frontiers in Immunology, 2024)
The genesis and progression of tumors are multifaceted processes influenced by genetic mutations within the tumor cells and the dynamic interplay with their surrounding milieu, which incessantly impacts the course of cancer.The tumor microenvironment (TME) is a complex and dynamic entity that encompasses not only the tumor cells but also an array of non-cancerous cells, signaling molecules, and the extracellular matrix.This intricate network is crucial in tumor progression, metastasis, and response to treatments. The TME is populated by diverse cell types, including immune cells, fibroblasts, endothelial cells, alongside cytokines and growth factors, all of which play roles in either suppressing or fostering tumor growth. Grasping the nuances of the interactions within the TME is vital for the advancement of targeted cancer therapies.Consequently, a thorough understanding of the alterations of TME and the identification of upstream regulatory targets have emerged as a research priority.NF-κB transcription factors, central to inflammation and innate immunity, are increasingly recognized for their significant role in cancer onset and progression.This review emphasizes the crucial influence of the NF-κB signaling pathway within the TME, underscoring its roles in the development and advancement of cancer. By examining the interactions between NF-κB and various components of the TME, targeting the NF-κB pathway appears as a promising cancer treatment approach.